MODEL PENGEMBANGAN KURIKULUM KEWIRAUSAHAAN DI PESANTREN BUSTANUL FALAH BANYUWANGI - Fauzi, Alex Haris; Yudha, Firma (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
Pesantren is the oldest Islamic educational institution in Indonesia. Now its presence has undergone many changes, including in the development of its curriculum. In the implementation of education, the Pesantren Bustanul Falah Banyuwangi develops an entrepreneurship curriculum by establishing a formal educational institution in the form of a Bustanul Falah vocational high school (SMK). This study aims to describe the planning, implementation, and evaluation of the entrepreneurship curriculum at the Islamic Boarding School Bustanul Falah Banyuwangi. This research is research that uses a descriptive qualitative approach. This research data comes from primary and secondary data. Data collection techniques were carried out using observation, interview, and documentation techniques. Furthermore, the collected data is interpreted and analyzed according to data analysis techniques, namely data reduction, data presentation, and conclusion drawing. This study found several findings, namely: first, the curriculum planning stage begins with the formulation of curriculum objectives, which is followed by the formulation of the entrepreneurship curriculum at the Bustanul Falah Islamic Boarding School Banyuwangi. Second, at the curriculum implementation stage, information was found about several policies implemented in curriculum development, the ability of teachers to implement the curriculum, and some of the obstacles faced in developing the entrepreneurship curriculum. Third, the evaluation stage is an evaluation of an objective model that is carried out at the end of curriculum development activities or better known as summative evaluation.